Types of Professional Interactions in Modern Russian Nannies: A Social Psychological Analysis - Drobysheva, T.V.; Romanovskaya, M.A. (Socialʹnaâ Psihologiâ i Obŝestvo, 2015)
The article describes the concept of the crowd proposed by a Russian lawyer and public The article presents results of a social psychological study of professional interactions in modern Russian nannies. It provides the first ever descriptions of significant interactions between nannies, employers and children. Four types of professional interactions are identified empirically depending on work motivation of nannies. Nannies with an attitude of "the child's older friend" are focused on establishing a close psychological relationship with the child. Their professional interaction with the child can be defined as overprotective. "Nannies-intermediaries" are more aware of their employee status and avoid breaking the psychological distance both with the child and the parents. The choice of interaction strategies in nannies with a "neighbor babysitter" attitude is determined mostly by their desire to gain work experience in their free time. They generally prefer not to establish close relationships with the child. The most professional of all are nannies with an attitude of "servants". They know how to resolve conflicts between children, how to arrange game activities for children, and conform to the requirements set by the parents. However, nannies of this type are more likely to physically suppress the will of the child. В статье представлены результаты социально-психологического исследования профессионального взаимодействия современных российских нянь. Впервые описаны значимые ситуации взаимодействия нянь с работодателями и воспитанником. Эмпирически выявлены четыре типа профессионального взаимодействия нянь, различающиеся в зависимости от мотивации выбора деятельности. Няни с позицией «старшая подруга ребенка» ориентированы на установление близкой психологической дистанции с воспитанником. Их профессиональное взаимодействие с воспитанником характеризуется гиперопекой.